Effectiveness of next generation science standards based 5e learning model by utilizing local potential - Rahmita Rahmita; Dadan Rosana (Jurnal Inovasi Pendidikan IPA, 2020)
This study aims at revealing the effectiveness of the next generation science standards based 5E learning model by utilizing the local potential of environmental education centre Puntondo to enhance students’ data literacy and problem-solving abilities. This research can be categorized as an experimental study. The subjects of this study were the seventh grade students of State Junior High School 2 Takalar. Two classes were involved, totaling 64 students. The data collection technique was carried out by using the test instrument. The data analysis technique used the gain score test and t-test analysis. The results showed that the gain score for the two classes for both abilities was in the medium category, with a value indicating that the gain from the experimental class was greater than the control class. Meanwhile, the t-test value is Sig. (2.tailed) data literacy of 0.003 and problem solving of 0.008. The acquisition of the value of the two abilities shows that the Sig. (2.tailed) is less than 0.05. Based on the research results, it can be concluded that the NGSS-based 5E learning model by utilizing the local potential of EEC Puntondo is considered effective to enhance the data literacy and problem-solving abilities.